Педагогічні умови забезпечення соціалізації дітей передшкільного віку в художньо-перетворювальній діяльності - Полікарпова, Марія Наджафівна (My University, 2023)
Наукова робота присвячена аналізу такого аспекту проблеми соціалізації дітей передшкільного віку засобами художньо-перетворювальної діяльності. Проаналізовано основні наукові підходи до соціалізації особистості у період передшкільного дитинства. Розкрито соціалізуючий потенціал художньо-перетворювальної діяльності щодо дітей передшкільного віку. Здійснено діагностику соціалізованості дошкільників у процедурі проведення констатувального експерименту. Розроблено критерії та показники, виявлено та обґрунтовано рівня соціалізованості дітей передшкільного віку засобами художньо-перетворювальної діяльності. Визначено педагогічні умови соціалізації дітей передшкільного віку засобами художньо-перетворювальної діяльності та розроблено методичні матеріали щодо забезпечення кожної із цих умов.
Polikarpova M.N. Pedagogical conditions of socialization of preschool children in artistic and creative activities / Polikarpova M.N. Qualification work. Nizhin, 2023. 90 p. The scientific work is devoted to the analysis of this aspect of the problem of socialization of preschool children by means of artistic and transformative activities. The main scientific approaches to personality socialization during preschool childhood are analyzed. The socializing potential of artistic and transformative activities for preschool children is revealed. The diagnosis of the socialization of preschoolers was carried out in the procedure of conducting a ascertaining experiment. Criteria and indicators have been developed, the level of socialization of preschool children through artistic and transformative activities has been identified and substantiated. Pedagogical conditions for the socialization of preschool children by means of artistic and transformative activities have been determined, and methodical materials have been developed to ensure each of these conditions. Key words: socialization, socialization of preschool children, subject activity, subject-transformative activity, artistic-transformative activity, preschool children.
Keywords: соціалізація; соціалізація дітей дошкільного віку; предметно-перетворювальна діяльність; художньо-перетворювальна діяльність; діти передшкільного віку